PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Sinta Rahmayanti Safitri; Widodo Budhi (Universitas Sarjanawiyata Tamansiswa, 2017)
This study is descriptively aimed to determine the tendency of science learning outcomes of students of grade VIII SMP Negeri 4 Wonosari academic year 2016/2017 through inquiry learning model and direct learning model in terms of student learning independence. Comparative to know the difference of science learning outcomes of students of class VIII SMP Negeri 4 Wonosari academic year 2016/2017 which learning using inquiry model of learning and direct learning model in terms of student learning independence. The type of this research is a Quasi experiment. Descriptive research results show that the tendency of science learning outcomes of students of grade VIII SMP Negeri 4 Wonosari academic year 2016/2017 whose learning using inquiry learning model included in the category very high and who use direct learning model included in the high category, student learning independence using model Inquiry learning is included in the high category, while learning independence using direct learning model is included in medium category. Comparatively, there is a very significant difference of science learning outcomes of students of grade VIII SMP Negeri 4 Wonosari academic year 2016/2017 which learning using inquiry learning model and direct learning model in terms of student learning independence.